STUDI FENOMENOLOGI: PENGALAMAN GURU DALAM MENERAPKAN PENILAIAN PORTOFOLIO DIGITAL PADA PEMBELAJARAN TEKS BIOGRAFI KELAS XI SMA - Adi Purnomo; Syamsul Sodiq; Miftachul Amri; Henry Trias Puguh Jatmiko (Universitas Muhammadiyah Surabaya, 2025)
This study aims to explore teachers' experiences in using digital portfolio assessment for biography texts in grade XI SMA. The research focuses on three main issues: (1) psychological and pedagogical changes in the application of technology, (2) technical and substantial problems encountered, and (3) the positive impact on students' writing ability. The subjective experiences of four Indonesian teachers were explored through interviews and portfolio document analysis. A qualitative research method with a phenomenological approach was used in this study. Results showed that teachers experienced a dilemma between enthusiasm for the benefits of digital portfolios and anxiety about the technology due to limited capabilities. One of the main issues included infrastructure problems, the problem of designing an assessment rubric that matches the features of biographical texts, and the additional task of providing feedback. However, digital portfolios have been shown to improve students' writing skills, especially in terms of text organisation, language use, and analysis of characters' values. This study suggests creating a broad teacher training model that incorporates technology based on contextual needs, and creating guidelines for assessing digital portfolios of biography texts more specifically. These results enhance the literature on evaluation for learning in the Indonesian educational context and aid the development of authentic assessment practices in the digital era.